Função ambiental das terras indígenas e mecanismos de efetividade - Abi-Eçab, Pedro (2012)
As a result of the supremacy of the general public environmental interests, as well as of all current and future inhabitants of the planet (The Constitution of the Republic, art. 225, caput), the indigenous lands, with no prejudice to the mission to ensure a life with dignity to the Indians, according to their customs and traditions (CR, art. 231), have an environmental role to perform, which gives rise to duties to said people, to the society and to the Public Power. According to this thesis, this work is intended to the analysis of the specially protected Indians lands as territorial units (CR, art. 225, § 1, III), defined with the purpose to ensure the preservation of the environment, the legal set of interactions and elements containing the ecologically balanced natural environment and the indigenous cultural assets (art. 231, § 1, art. 215, § 1 e art. 216, caput). It is, thus, a territorial unit affected, not only for the physical and cultural survival of the indigenous population, but also for the protection of compounds such as the set of environmental interactions and elements, such as the biodiversity, the climatic balance, the hydrical, mineral, floristical and faunal resources. The indigenous property is ensured according to the traditionality criteria, as expressed under art. 231, caput, and repeated in paragraphs 1 and 2, implying on the use of the natural resources of low impact. The connection between Humanity and environment has been increasingly of unsustainability, with the paradigm of the good savage not acceptable, provided that the indigenous populations, when accessing technology and new habits, experiment an ethnic transfiguration and also start to promote the environmental degradation. There is, therefore, a challenge to the Public Power, the society and to the people in question: to find a way for the sustainable development, (responsibility) as to the social, cultural and environmental rights. This work proposes that the indigenous rights shall not overweight the right to the ecologically balanced environment. The indigenous lands exist in order to harmonize these two general public interests, to the benefit of the current and future generations in the whole planet, and to the indigenous themselves. The key instruments for the legalization of this environmental function are analyzed, as well